Using a competitive counterflow assay to identify novel cationic substrates of OATP1B1 and OATP1B3 - Schnegelberger, Regina D.; Steiert, Brianna; Sandoval, Philip J.; Hagenbuch, Bruno (Frontiers in Physiology, 2022)
OATP1B1 and OATP1B3 are two drug transporters that mediate the uptake of multiple endo- and xenobiotics, including many drugs, into human hepatocytes. Numerous inhibitors have been identified, and for some of them, it is not clear whether they are also substrates. Historically radiolabeled substrates or LC-MS/MS methods were needed to test for transported substrates, both of which can be limiting in time and money. However, the competitive counterflow (CCF) assay originally described for OCT2 and, more recently, for OCT1, OATP2B1, and OATP1A2 does not require radiolabeled substrates or LC-MS/MS methods and, as a result, is a more cost-effective approach to identifying substrates of multidrug transporters. We used a CCF assay based on the stimulated efflux of the common model substrate estradiol-17β-glucuronide (E17βG) and tested 30 compounds for OATP1B1- and OATP1B3-mediated transport. Chinese Hamster Ovary (CHO) cells stably expressing OATP1B1 or OATP1B3 were preloaded with 10nM [3H]-estradiol-17β-glucuronide. After the addition of known substrates like unlabeled estradiol-17β-glucuronide, estrone-3-sulfate, bromosulfophthalein, protoporphyrin X, rifampicin, and taurocholate to the outside of the preloaded CHO cells, we observed efflux of [3H]-estradiol-17β-glucuronide due to exchange with the added compounds. Of the tested 30 compounds, some organic cation transporter substrates like diphenhydramine, metformin, and salbutamol did not induce [3H]-estradiol-17β-glucuronide efflux, indicating that the two OATPs do not transport them. However, 22 (for OATP1B1) and 16 (for OATP1B3) of the tested compounds resulted in [3H]-estradiol-17β-glucuronide efflux, suggesting that they are OATP substrates. Among these compounds, we further tested clarithromycin, indomethacin, reserpine, and verapamil and confirmed that they are substrates of the two OATPs. These results demonstrate that the substrate spectrum of the well-characterized organic anion transporting polypeptides includes several organic cations. Furthermore, as for other drug uptake transporters, the CCF assay is an easy-to-use screening tool to identify novel OATP substrates.